IMPROVING STUDENTS’ MASTERY ON THE USE OF SIMPLE PAST TENSE THROUGH INDUCTIVE METHOD - elyani, Veronikai Dewi; Susilawati, Endang; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is aimed at describing how the Inductive method improvesstudents’ mastery on the use simple past tense on the eighth grade students ofSMP N 1 Sungai Raya in academic year 2017/2018. Based on the observations,the students had problems on the use of simple past tense. The research wasconducted Class Room Action Research in three cycles. The inductive methodwas selected to solve the problem. There are four steps in using inductivemethod. The students were giving a set of examples; generalize a grammaticalrule, test the grammatical rule against in new sentences and revise thegrammatical rule. The researcher used observation and students’ writingassessment to collect the data. The researcher also used observation checklist,field note and students’ assessment to get the research finding. The finding ofthis research indicated that the inductive method was successful. It showed inthe first step the students know about tenses is used in the sentences. Theyknow how to formulate the rule by analyzing the example in second step. Thirdsteps students were able to write simple pas tense correctly and the last stepsstudents could analyze the rule in the sentence. There were thirty four of thirtysix students already achieved the target score seventy five based on KKM. Itmeans 94 % students could achieve the standard score. In conclusion, InductiveMethod improved students’ mastery on the use simple past tense. Key words: Mastery, simple past tense, Inductive Method.